The Effect of Adding Natural Supplements on the Omega-3 Content of Quail Eggs as a Solution to Stunting Prevention in Indonesia - Gagah Hendra Wijaya (Musamus Journal of Livestock Science, 2023)
Omega-3 fatty acids are critical for the growth and regeneration of brain cells, although fish consumption is still very low in this regard. Furthermore, there are indications that the products originating from the sea are becoming contaminated, so there is an urgent need to add omega-3 fatty acids to the food that the average citizen eats. An effort that can be made is to produce eggs from quail, which are high in essential fatty acids, particularly low-cholesterol omega-3 fatty acids. The method used in this research was adding natural suplements containing omega-3 to drinking water. Based on the results of the analysis it is known that quail eggs have been treated with the addition of natural supplements produce quail eggs that contain omega-3, 6 and 9, which are good for health. The intended outcome is a product that could prevent stunting in Indonesia. Keywords: Quail eggs, Omega-3, Natural suplement, Stunting